2022
DOI: 10.1155/2022/5741787
|View full text |Cite
|
Sign up to set email alerts
|

The Recognition Method of Athlete Exercise Intensity Based on ECG and PCG

Abstract: Athletes usually arrange their training plans and determine their training intensity according to the coach’s experience and simple physical indicators such as heart rate during exercise. However, the accuracy of this method is poor, and the training plan and exercise intensity arranged according to this method can easily cause physical damage, or the training cannot meet the actual needs. Therefore, in order to realize the reasonable arrangement and monitoring of athletes’ training, a method of human exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Through a large number of mathematical model processing and statistical analysis, some researchers found that there is an exponential decay relationship between heart rate(HR) and heart rate variability(HRV) [18]. Studies have proved that the power spectrum of heart rate variability is affected by exercise intensity [19]. Both heart rate and heart rate variability come from the electrical signals of the heart, which indicated that the electrical signals contain movement information.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Through a large number of mathematical model processing and statistical analysis, some researchers found that there is an exponential decay relationship between heart rate(HR) and heart rate variability(HRV) [18]. Studies have proved that the power spectrum of heart rate variability is affected by exercise intensity [19]. Both heart rate and heart rate variability come from the electrical signals of the heart, which indicated that the electrical signals contain movement information.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…The physiological signals are useful for monitoring and assessing the physical status of athletes. Wang and Zhu carried out an interesting research work on monitoring and categorizing the body exercise intensity conditions by means of electrocardiogram (ECG) and phonocardiogram (PCG) signal analysis [ 9 ]. The ECG and PCG signals were first projected onto an image with various motion intensity annotations.…”
Section: Introductionmentioning
confidence: 99%
“…The ECG and PCG signals were first projected onto an image with various motion intensity annotations. The AlexNet CNN architecture that contained five conventional layers, one pooling layer, and three fully connected layers was employed to perform the classifications of body exercise intensities of athletes [ 9 ]. With the purpose of visualizing the cluster scatters, the t-SNE technique was used to reduce the data dimensions in the fully connected layers of the AlexNet architecture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation